Influence of Europa's Time‐Varying Electromagnetic Environment on Magnetospheric Ion Precipitation and Surface Weathering. Issue 5 (27th April 2021) - Addison, Peter; Liuzzo, Lucas; Arnold, Hannes; Simon, Sven
Abstract: We combine the electromagnetic fields from a hybrid model with a particle‐tracing code to calculate the time‐varying spatial distribution of magnetospheric ion flux onto the surface of Jupiter's moon Europa. The electromagnetic fields at Europa are perturbed by the sub‐alfvénic interaction of the moon's ionosphere and induced dipole with the magnetospheric plasma. These perturbations substantially modify magnetospheric ion trajectories at all energies. We calculate spatially resolved surface flux maps of thermal and energetic ions for various distances between Europa and the center of Jupiter's magnetospheric plasma sheet. The upstream ion distributions are constrained through in‐situ particle data from the Galileo and Juno spacecraft. These maps are then combined to obtain the average distribution of magnetospheric ion surface flux over a full synodic rotation. Our results show that the draping and pileup of the magnetic field reduce ion flux onto Europa's trailing hemisphere by several orders of magnitude, while a significant number of the incident ions are deflected onto the leading hemisphere. Taking into account the deflection of energetic ions in the draped electromagnetic fields shifts the region of minimum energetic ion surface flux from Europa's wakeside equator to its ramside equator. This generates an "inverted bullseye" pattern of energetic ion flux centered at the trailing apex. Despite drastic changes to the morphology of the ion surface flux when the alfvénic plasma interaction is included, we still find a strong correlation between variations of sulfuric acid concentration observed across Europa's surface by Galileo and our modeled sulfur influx pattern. Key Points: Magnetic field draping around Europa reduces ion surface flux onto the upstream hemisphere and enhances flux onto its downstream hemisphere Europa's upstream hemisphere receives the least amount of flux from energetic magnetospheric ions The flux pattern of sulfur ions is strongly correlated to observed surface variations in sulfuric acid concentration measured by Galileo